Information Communication Technology as A Tool for Improving Nigerian Education at All Levels: A Theoretical Perceptive - Florence Olutunu Daramola; Gboyega Ayodeji Aladesusi (Universitas Pendidikan Ganesha, 2022)
The importance and integration of ICT equipment and facilities in teaching and learning are needed in Nigerian schools. However, the use of ICT in learning is still experiencing problems. The aims of this study are information and communication technology as a tool to improve Nigerian education at all levels. This type of research is qualitative research. The methods used in data collection are documentation study, literature study, and observation. The primary data collection instrument is the researcher observing, asking, listening, asking, and taking research data in qualitative research. The data analysis technique used is descriptive qualitative analysis. The result of the research is that Nigeria is experiencing problems with the integration and application of ICT tools due to many factors such as; Limited ICT facilities in Nigerian Schools, Lack of experienced technical tutors, Electrical Problems, Environmental Factors, and Expensive IC tools, and Lack of professional skills. The research concludes that the government should make efforts to offer solutions to the problems mentioned in this paper to improve Nigerian education at all levels. The researcher asks education stakeholders to encourage tutors, facilitators, and students to develop positive attitudes towards using ICT tools at all levels of education in Nigeria.